2018
DOI: 10.14814/phy2.13792
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet effects on amniotic fluid volume and amnion aquaporin expression in non-human primates

Abstract: Western style, high‐fat diet (HFD) and associated high lipid levels have deleterious effects on fetal and placental development independent of maternal obesity and/or diabetes. Our objectives were to determine whether HFD without development of obesity would alter amniotic fluid volume (AFV) and amnion aquaporin (AQP) expression in a non‐human primate model. Japanese macaques were fed either a control diet or HFD before and during pregnancy. The four quadrant amniotic fluid index (AFI) was used as an ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Of interest, analysis of regional differences in amnion gene expression demonstrated that VEGF and sFlt-1 levels differed among the three regions with VEGF expression lowest in secondary placental amnion and highest in reflected amnion, while sFlt-1 expression lowest in the primary placental amnion but highest in the reflected amnion. These regional differences were consistent with the differential gene expression profiles characteristic of different amnion regions (Han et al 2008), as well as with the differential aquaporin gene expression shown in our recent HFD pregnant macaque (Cheung et al 2018) and human (Bednar et al 2015) studies. The significance of such differences is unclear and may be related to the permeability characteristics of the three amnion regions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Of interest, analysis of regional differences in amnion gene expression demonstrated that VEGF and sFlt-1 levels differed among the three regions with VEGF expression lowest in secondary placental amnion and highest in reflected amnion, while sFlt-1 expression lowest in the primary placental amnion but highest in the reflected amnion. These regional differences were consistent with the differential gene expression profiles characteristic of different amnion regions (Han et al 2008), as well as with the differential aquaporin gene expression shown in our recent HFD pregnant macaque (Cheung et al 2018) and human (Bednar et al 2015) studies. The significance of such differences is unclear and may be related to the permeability characteristics of the three amnion regions.…”
Section: Discussionsupporting
confidence: 90%
“…The absence of HFD effects on amnion VEGF and sFlT‐1 gene expression are similar to findings in our recent study of pregnant macaques fed a HFD (Cheung et al. ) in that expression levels of five aquaporins in the amnion was not affected by the high fat intake in animals with the resistant phenotype. Of interest, analysis of regional differences in amnion gene expression demonstrated that VEGF and sFlt‐1 levels differed among the three regions with VEGF expression lowest in secondary placental amnion and highest in reflected amnion, while sFlt‐1 expression lowest in the primary placental amnion but highest in the reflected amnion.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations